Arguing the just war in Islam - Kelsay, John, 1953- (Cambridge, Mass. : Harvard University Press, 2007)
"This book provides a systematic account of how Islam's central texts interpret jihad, guiding us through the historical precedents and Qur'anic sources upon which today's claims to doctrinal truth and legitimate authority are made. In illuminating the broad spectrum of Islam's moral considerations of the just war, Kelsay helps Muslims and non-Muslims alike make sense of the possibilities for future war and peace."--BOOK JACKET.
1. Sources -- 2. Shari'a Reasoning -- 3. Politics, Ethics, and War in Premodern Islam -- 4. Armed Resistance and Islamic Tradition -- 5. Military Action and Political Authority -- 6. Muslim Argument and the War on Terror.
Formerly CIP.
Includes bibliographical references and index.
Keywords: War -- Religious aspects -- Islam; Islam and politics